The moth-keeper - O'Neill, Katie (Cartoonist) (RH Graphic, 2023)
Anya is excited to prove her worth as a Moth Keeper, a protector of the lunar moths that allow the Night-Lily flower to bloom once a year, but she quickly finds that life as a Moth Keeper is not what she imagined it would be.